Hubungan Gaya Pengurusan Konflik dengan Jenis Personaliti Guru-Guru Asrama di Terengganu - Zaleha, Mohd Yusoff (1996)
The aim of this study was to identified the conflict management styles and the personality type preferences among school wardens in Terengganu. This study was also to investigate the relationship between the conflict management styles and personality type preferences and demographic factors of wardens. A total of 28 of schools in Terengganu that have ‘harian’ hostels (26 ) and ‘desa’ hostels (2) were selected for the research. From the 92 questionnaires distributed, only 80 (87%) were usable. The questionnaires consisted of 66 items which includes 4 items on demographic factors, 30 items on conflict management styles adapted from the Thomas-Kilmann Conflict Mode Instrument (T-KCMI), and 32 items on personality types adapted from Myers-Briggs Type Indicator (MBTI) by Dr. R. Craig Hogan and Dr. David W. Champagne. Data were analyzed using descriptive statistics of frequencies, percents, means, standard deviations and phi. To determine the relationship between conflict management styles and the personality types, Davis (1971) interpretation were used. The finding of the study showed that the main conflict management style was to be the avoidance style (46.3%) which implies that most of the school wardens when confronting with conflicts will resolve using the avoidance style. Where as, the most preferred personality type was to be ESTJ ( 42.5%). The result also revealed that there were differences in conflict management styles between genders. Female wardens were more inclined to avoidance style while male were more inclined to collaborative and accomadative styles. There were no differences in conflict management styles with regard to age, years of service as warden, and academic achievement of respondents. School wardens who favored the extrovert, sensing and judgement were more apt to use the avoidance style than were the introvert, intuitive and perceiving personality type preferences. A negligible association (phi=0.05) was found between conflict management style and the thinking/feeling personality type preferences. Therefore, the thinking/feeling personality type preferences did not affect the choice of conflict management styles. The extrovert/introvert (phi=0.32) was the most personality type preferences that affect the conflict management styles rather than sensing/intuitive (phi=0.24) and judging/perceived personality types (phi=0.10).